2016
DOI: 10.1590/1809-98232016019.150110
|View full text |Cite
|
Sign up to set email alerts
|

Falls among the non-institutionalized elderly in northern Minas Gerais, Brazil: prevalence and associated factors

Abstract: Objective: To identify the prevalence of falls and associated factors in non-institutionalized elderly persons. Methods: A cross-sectional study featuring a population-based sample of non-institutionalized elderly persons in a city in the north of Minas Gerais was performed. Interviews were conducted in households by trained staff using validated instruments. We investigated the associations between falls and demographic, socioeconomic and health-related factors. After bivariate analysis, the variables associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
3
21

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 33 publications
(48 reference statements)
6
10
3
21
Order By: Relevance
“…The marital situation was not associated with the fall event, corroborating a study developed with 683 non-institutionalized older people (21) . In both investigations, the population living with a partner was predominant, being married, in a stable union or with a significant other.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The marital situation was not associated with the fall event, corroborating a study developed with 683 non-institutionalized older people (21) . In both investigations, the population living with a partner was predominant, being married, in a stable union or with a significant other.…”
Section: Discussionsupporting
confidence: 82%
“…Focchesatto, Rockett and Perry (28) studied 70 individuals aged 60 years or older residing in the rural area of Rio Grande do Sul, where systemic arterial hypertension, osteoporosis and dyslipidemia were the most reported diseases by the participants. Differently from this research, Carneiro et al (21) showed that some investigated diseases, although associated in a bivariate analysis, were not maintained in the final model. The presence of chronic diseases in aging is a public health problem with high prevalence and important consequences, corroborating the finding in a study that investigated the prevalence and distribution of multimorbidity in Brazilian older people, in which only 6.0% of the sample did not show chronic disease.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Our findings showed that DOH was associated with low OHL after adjusting for other covariates, confirming previous evidence that subjective perceptions of oral health in older persons are a multifactorial issue. [5][6][7][8][23][24][25][26][27][28][29] Approximately 21% of participants in our study were dissatisfied with their oral health, similar to other national 30 TA B L E 1 Sample characteristics and associations with satisfaction with oral health among older people in Piracicaba, Brazil oral health showed positive features. 34 One hypothesis for these contradictory results between normative and subjective aspects in the elderly population can be associated with the social representations related to oral health that are constructed throughout their lives in which the deterioration of dental status is depicted as a natural phenomenon of ageing.…”
Section: Discussionsupporting
confidence: 67%